Restructuring and the loss of preferences : labour challenges for the Caribbean banana industry - Nii Addy, David (2000)
Looks at some of the implications of the current changes underway in the international environment, for the Windward Islands banana industry. Focuses on the major banana producing countries of the OECS i.e. Dominica, St. Lucia, St. Vincent and the Grenadines as well as to a lesser degree Grenada.